Clinical and Histopathological Presentation of Abnormal Uterine Bleeding in Perimenopausal Women in Tertiary Center of Nepal - Chapagain, Sadikchha; Dangal, Ganesh (Journal of Nepal Health Research Council, 2020)
Background: Abnormal uterine bleeding is defined as any bleeding outside of normal menstruation pattern with excessive duration, frequency, and amount and it is a common problem among women of reproductive age group with varied presentations. The aim of the study was to correlate the histopathological finding in patients with abnormal dysfunctional uterine bleeding with the presenting clinical feature. Methods: A prospective cross sectional study was carried out at Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu during the period of one year (February 2019 to January 2020). It included 77 perimenopausal women with abnormal uterine bleeding who presented in gynecology outpatient department and planned for dilatation and curettage. Then the participants were counselled and informed consent was taken. Histopathological reports reviewed and analysis done. Results: The most common age group of women presenting with abnormal uterine bleeding was 40 to 44 years and the commonest clinical feature was menorrhagia (31/77, 40.3%) followed by menometrorrhagia (18/77, 23.4%). Majority of women were multiparous, parity 3 to 4 (38/77, 49.4%). Proliferative endometrium (29/77, 37.7%) was most common histopathological findings followed by secretory endometrium (24/77, 31.2%). Proliferative endometrium was more commonly associated with menorrhagia and menometrorrhagia whereas secretory endometrium with metrorrhagia (P-value 0.000). Conclusions: Menorrhagia and Menometrorrhagia are the most common clinical presentation among perimenopausal women with AUB, whereas proliferative endometrium and secretory endometrium were the common histopathological findings respectively.Accurate diagnosis is crucial for a selection of relevant treatment and avoidance of unnecessary major surgical procedure. Keywords: Abnormal uterine bleeding; endometrium; histopathology; perimenopausal.